Optimization of PG70 Asphalt Mixtures Through the Addition of Palm Kernel Shell Ash - Septi Adnan Adnan; Arya Dirgantara Arya; Haerul Purnama Haerul; Aidhil Saputra Syahwal Aidhil (Universitas Sulawesi Barat, 2026)
This study aims to determine the effect of adding palm kernel shell ash to PG70 modified asphalt mixtures using the Marshall method. This study was motivated by the high volume of palm kernel shell ash waste. The study was conducted with variations in palm kernel shell ash content of 0%, 2%, 4%, and 6% by weight of the total aggregate. The parameters tested included stability, flow, VIM, VMA, VFB, and the Marshall Quotient (MQ). The results showed that the addition of palm kernel shell ash increased the stability and density of the mixture. The optimum content was obtained at a 4% ash addition, where the stability value reached its maximum limit, providing a balance between stability, workability, and void content in the mixture. Thus, palm kernel shell ash can be used as an alternative filler material in PG70 modified asphalt mixtures that is more environmentally friendly and economically viable.